The Secreted Plant N-Glycoproteome and Associated Secretory Pathways - Ruiz-May, Eliel; Kim, Sang Jin; Brandizzi, Federica; Rose, Jocelyn K. (Frontiers in Plant Science, 2012)
N-Glycosylation is a common form of eukaryotic protein post-translational modification, and one that is particularly prevalent in plant cell wall proteins. Large scale and detailed characterization of N-glycoproteins therefore has considerable potential in better understanding the composition and functions of the cell wall proteome, as well as those proteins that reside in other compartments of the secretory pathway. While there have been numerous studies of mammalian and yeast N-glycoproteins, less is known about the population complexity, biosynthesis, structural variation and trafficking of their plant counterparts. However, technical developments in the analysis of glycoproteins and the structures the glycans that they bear, as well as valuable comparative analyses with non-plant systems, are providing new insights into features that are common among eukaryotes and those that are specific to plants, some of which may reflect the unique nature of the plant cell wall. In this review we present an overview of the current knowledge of plant N-glycoprotein synthesis and trafficking, with particular reference to those that are cell wall localized.